Oltre L’intelligenza Artificiale - Pieretti, Antonio (Hermeneutica, 2020)
We are entering the information age, because of the unbelievable amount of data we have. Big Data Technologies tend to structure the world and humans in order to adapt them to their limited capabilities. Man, because of his intelligence, differs from machines; in fact he has the ability not only to process data, but also to interpret and understand them, therefore to give them meaning. But, in the exercise of this activity, he works as a mean and not as an end in itself. Therefore, his personal identity coincides with the function he performs, that is, with his informational identity. This conclusion, however, contradicts the thesis according to which artificial intelligence is only reproductive as opposed to human intelligence. This, in turn, cannot behave like machines, because it cannot do without the body or the world of life.